Analysis of Added Value and Development Strategy for The Coconut-Based Food Industry in North Sulawesi Province - Herry F. Pinatik; Dedie Tooy; Maya Hendrietta Montolalu; Denny Saroinsong; Asnidar Mastam; Mukhlis Mukhlis; Teltje Koapaha; Rine Kaunang (Postgraduate, University of Mataram, 2025)
Problems in developing the coconut-based creative industry in North Sulawesi Province include limited business capital and modern processing technology, inconsistent product quality, and weak promotion and marketing. As a result, the Micro, Small, and Medium Enterprises (MSMEs) sector is unable to maximize the potential of coconuts as a significant source of added value. This study aims to examine the added value of coconut-based food products and formulate policy strategies for the development of coconut-based creative industries MSME level. The research method is added value analysis using the Hayami (1987) approach and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) for policy strategy formulation. The results of the study show that the output value of coconut-based food products reaches IDR 250,000 per unit, with an added value of IDR 25,214 per product and an added value ratio of 71%. Labor compensation is recorded at IDR 3,044 per kilogram or 12% of the added value, while the profit obtained is IDR 22,170 per product or 88%. SWOT analysis recommends a development strategy oriented towards a combination of S-O (Strengths–Opportunities) and W-O (Weaknesses–Opportunities), through improving production capacity and quality, strengthening promotion, and building partnerships with stakeholders, facilitated by the local government